Ultra-Small Gold Nanoparticles with Mild Immunomodulatory Activity as a Potential Tool for Bio-Applications - Bělinová, T; Javorová, P; Nguyenová, H. Y; Řezníčková, A; Humlová, Zuzana; Hubálek Kalbáčová, Marie (Folia biologica (Praha), 2022)
Recently, more and more efforts are directed towards developing new imaging and drug-delivery options based on various nanoparticles, exploiting their unique properties. Here, ultra-small gold nanoparticles functionalized with widely used polyethylene glycol and its amine-terminated form were tested in respect of their potential interactions with human immune cells (cell line and primary cells). The results showed that differently terminated ultrasmall gold nanoparticles represent an interesting theranostic platform as they are harmless to immune cells (not inducing cytotoxicity and severe immune response) and on the other hand, they can serve as imaging and/or drug delivery agents using e.g. monocytes/ macrophages as "Trojan horses" to deliver these nanoparticles across the blood-brain barrier and diagnose or treat pathologies of the central nervous system.
Keywords: aminy; kovové nanočástice; Polyethylene Glycols; polyethylenglykoly; Amines; Gold; Metal Nanoparticles; lidé; zlato; Humans